PEMBINAAN PENGELOLAAN KEUANGAN KELUARGA DAN PENINGKATAN KEMAMPUAN BAHASA INGGRIS PADA IBU RUMAH TANGGA DI PERUMAHAN GRIYA TAHAP 1 BATU AJI - Hikmah; Ance Jusmaya (ASOSIASI IDEBAHASA KEPRI, 2020)
Being a housewife is a multi-tasking tasks and it is not an easy thing. In this case, a housewife has many roles such as should be a mother , a counselor for her daughter as well as taking care of everything. Besides, the mother is also a teacher. As we know that, the first teacher of a child is a mother. Then, the mother is also a financial manager and general administration at home. Many problems have been encountered, so a housewife tasks are very hard, in this case they have to harmonize and regulate the amount of income and increase in some basic needs and daily needs. Except the problems that regarding with financial management, the problem face also relates with the lack of knowledge of housewives in English. As a housewife needs an ability of English skill to help their children in studying later on. Those phenomenon happens in families who live in Griya Batu Aji stage 1.The solution offered housewife that a family financial management is very important for financial survival of a family. As a financial manager at home, a housewife must be able to manage expenditure and income posts. Besides, for teaching English, parents should implement a fun learning environment and learning strategies that can motivate children to learn English. A learning environment that suits the real-world context is needed so that parents can apply it to everyday learning activities with children.